2017
DOI: 10.1016/j.amjcard.2017.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Usefulness of Cardiopulmonary Exercise Testing for Managing Patients With Severe Aortic Stenosis

Abstract: The approach to managing asymptomatic or questionably symptomatic patients for aortic stenosis is difficult. We aimed to determine whether cardiopulmonary exercise testing (CPET) is prognostically useful in such patients. Patients judged asymptomatic or questionably symptomatic for aortic stenosis with aortic valve area index <0.6 cm/m and left ventricular ejection fraction ≥0.50 were managed conservatively provided they had either (group 1) normal peak oxygen consumption and peak oxygen pulse (>83% and >95% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Maximal exercise tests are generally restricted to asymptomatic AS patients since maximal effort in truly symptomatic patients with AS is considered an absolute contraindication 1,2 . Strict "contraindication" to exercise testing becomes ambiguous in patients who are sedentary since pertinent symptoms may only become apparent during exercise provocation 1 as one-third of patients claiming to be asymptomatic may develop symptoms during exercise [3][4][5][6] . Given such a fine line between being symptomatic vs. asymptomatic, it is important to emphasize that a meta-analysis concluded that symptom-limited stress testing is safe and has an important prognostic value in patients with severe AS 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Maximal exercise tests are generally restricted to asymptomatic AS patients since maximal effort in truly symptomatic patients with AS is considered an absolute contraindication 1,2 . Strict "contraindication" to exercise testing becomes ambiguous in patients who are sedentary since pertinent symptoms may only become apparent during exercise provocation 1 as one-third of patients claiming to be asymptomatic may develop symptoms during exercise [3][4][5][6] . Given such a fine line between being symptomatic vs. asymptomatic, it is important to emphasize that a meta-analysis concluded that symptom-limited stress testing is safe and has an important prognostic value in patients with severe AS 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In the early seventies, Lee et al reported similar systemic hemodynamic improvements with reduced ventricular preload that closely matched the exercise-induced increase in oxygen consumption in 12 patients, 3 to 6 months following surgical aortic valve replacement. 11 As a maximal cardiopulmonary exercise test was deemed inappropriate and potentially dangerous in elderly patients with severe symptomatic AS, 12 we performed a submaximal bicycle exercise test that was safely conducted in all patients. As it integrates cardiopulmonary and musculoskeletal systems functioning, this test appears suitable for baseline screening, follow-up assessment, and research purposes, particularly among frail subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers conducting the studies included in this systematic review conducted CPET-IGR using varied testing protocols. Most of these were tests involving a progressive work rate [31,[59][60][61]63,[65][66][67][68][69][70][72][73][74][75][76][77][78][79][80]82,83,85,[93][94][95][96][97][98]101,102], while a few studies used constant load protocols in addition to progressive work rate tests [71,81,92,99,100].…”
Section: Protocols Used In Cpet-igr Studiesmentioning
confidence: 99%
“…Firstly, some of the studies included in this review were based on small patient groups [31,51,59,66,76,79], and most of the studies focused on patients with either healthy conditions or heart failure. There were few studies available that focused on other disease entities [85,89,[95][96][97][98][99]. Additionally, not all the required values could be obtained from the studies because they were not described.…”
Section: Limitationsmentioning
confidence: 99%